Strengthening of K3 (Safety System) and Risk Management for Students at Vocational School in the Context of Providing Internships based on Pancasila Student Competencies at SMKN 1 Banyuputih, Situbondo: Penguatan Sistem K3 dan Manajemen Resiko kepada Siswa-siswi SMK dalam Rangka Pembekalan Magang berbasis Kompetensi Pelajar Pancasila di SMKN 1 Banyupitih Kabupaten Situbondo - Mardiyanto, Mohammad; Kurnianto, Mokhamad Fatoni (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2025)
The introduction of K3 (Safety System) is one of the important aspects that must be known and implemented for students who will carry out apprenticeships. The implementation of the K3 system is closely related to the implementation of risk management. The implementation of the K3 system and risk management aims to identify potential dangers and control potential dangers and risks that exist in the industry. The aim of implementing this socialization is to strengthen students' abilities in identifying potential dangers and determining the appropriate type of control. The implementation of this socialization consists of 4 (four) stages including: 1) delivering material, 2) providing case studies in the form of teaching aids. 3) give assignments to students regarding potential dangers and control systems in the school environment, and 4) carry out evaluations and assessments regarding the work objects of each student. It is hoped that this activity will be able to provide students with an overview of potential hazards and their control systems in a specific and measurable manner.